\(\dfrac{1}{3}\times2\dfrac{1}{5}+\dfrac{1}{3}\times(-0,8)\)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a) \(3\times\dfrac{4}{11}=\dfrac{3\times4}{11}=\dfrac{12}{11}\)
b) \(1\times\dfrac{5}{4}=\dfrac{1\times5}{4}=\dfrac{5}{4}\)
c) \(0\times\dfrac{2}{5}=\dfrac{0\times2}{5}=\dfrac{0}{5}=0\)
a: \(=\dfrac{3\cdot4}{11}=\dfrac{12}{11}\)
b: \(=\dfrac{1\cdot5}{4}=\dfrac{5}{4}\)
c: \(=\dfrac{0\cdot2}{5}=0\)
a: Số số hạng là \(\dfrac{2018-2}{2}+1=1009\left(số\right)\)
Tổng là: \(\dfrac{2018+2}{2}\cdot1009=1009\cdot1010=1019090\)
b: \(10S=10^2+10^3+...+10^{101}\)
\(\Rightarrow9S=10^{101}-10\)
hay \(S=\dfrac{10^{101}-10}{9}\)
c: \(5S=1+\dfrac{1}{5}+...+\dfrac{1}{5^{99}}\)
\(\Leftrightarrow4S=1-\dfrac{1}{5^{100}}\)
hay \(S=\dfrac{1}{4}\left(1-\dfrac{1}{5^{100}}\right)\)
a,
\(\dfrac{\left(3^3\right)^{15}.5^3.\left(2^3\right)^4}{\left(5^2\right)^2.\left(3^4\right)^{11}.2^{11}}=\dfrac{3^{45}.5^3.2^{12}}{5^4.3^{44}.2^{11}}=\dfrac{6}{5}\)
b, \(\left(-\dfrac{14}{25}\right)^2.\dfrac{125}{49}+\left(-3\dfrac{11}{36}\right).2\dfrac{2}{17}=\dfrac{4}{5}.\left(-7\right)=-\dfrac{28}{5}\)
c, \(\dfrac{1}{3}-2.1=-\dfrac{5}{3}\)
`4 1/5 xx 2 1/4`
`= 21/5 xx 9/4`
`= 189/20`
__
`4 1/5 : 2 1/4`
`= 21/5 : 9/4`
`= 21/5 xx 4/9`
`=84/45`
`=28/15`
__
`3 3/5 xx 1 2/3`
`= 18/5 xx 5/3`
`= 90/15`
`=6`
__
`3 3/5 : 1 2/3`
`= 18/5 : 5/3`
`= 18/5 xx 3/5`
`=54/25`
\(4\dfrac{1}{5}\times2\dfrac{1}{4}\\ =\dfrac{21}{5}\times\dfrac{9}{4}\\ =\dfrac{21\times9}{5\times4}\\ =\dfrac{189}{20}\)
\(3\dfrac{3}{5}\times1\dfrac{2}{3}\\ =\dfrac{18}{5}\times\dfrac{5}{3}\\ =\dfrac{18\times5}{5\times3}\\ =\dfrac{90}{15}\\ =6\)
\(4\dfrac{1}{5}:2\dfrac{1}{4}\\ =\dfrac{21}{5}:\dfrac{9}{4}\\ =\dfrac{21}{5}\times\dfrac{4}{9}\\ =\dfrac{21\times4}{5\times9}\\ =\dfrac{84}{45}\\ =\dfrac{28}{15}\)
\(3\dfrac{3}{5}:1\dfrac{2}{3}\\ =\dfrac{18}{5}:\dfrac{5}{3}\\ =\dfrac{18}{5}\times\dfrac{3}{5}\\ =\dfrac{18\times3}{5\times5}\\ =\dfrac{54}{25}\)
a, \(4\times\left(-\dfrac{1}{2}\right)^3-2\times\left(-\dfrac{1}{2}\right)^2+3\times\left(-\dfrac{1}{2}\right)+1\)
\(=\left(-\dfrac{1}{2}\right)\left[\left(4\times-\dfrac{1}{2}\right)-\left(2\times-\dfrac{1}{2}\right)+3\right]+1\)
\(=\left(-\dfrac{1}{2}\right)\left(-2+1+3\right)+1\)
\(=\left(-\dfrac{1}{2}\right)2+1\)
\(=-1+1\)
\(=0\)
@Trịnh Thị Thảo Nhi
a, 4×(−12)3−2×(−12)2+3×(−12)+14×(−12)3−2×(−12)2+3×(−12)+1
=(−12)[(4×−12)−(2×−12)+3]+1=(−12)[(4×−12)−(2×−12)+3]+1
=(−12)(−2+1+3)+1=(−12)(−2+1+3)+1
=(−12)2+1=(−12)2+1
=−1+1=−1+1
=0=0
a: \(=\left(\dfrac{17}{10}+\dfrac{70}{10}-\dfrac{87}{10}\right):\left(\dfrac{23}{4}-\dfrac{11}{4}+\dfrac{9}{25}\right)\cdot\left(12,98\cdot0,25\right)+12,5\)
\(=0:\left(3+\dfrac{9}{25}\right)\cdot\left(12,98+0,25\right)+12,5\)
=12,5
b: \(=\dfrac{13}{12}\cdot\dfrac{27}{5}\cdot2\cdot\dfrac{34}{9}\cdot2\cdot\dfrac{2}{17}\)
\(=\dfrac{13}{12}\cdot2\cdot\dfrac{27}{5}\cdot\dfrac{34}{9}\cdot\dfrac{4}{17}\)
\(=\dfrac{13}{6}\cdot\dfrac{27}{5}\cdot\dfrac{8}{9}=\dfrac{8}{6}\cdot3\cdot\dfrac{13}{5}=4\cdot\dfrac{13}{5}=\dfrac{52}{5}\)
a) $\frac{2}{5} \times \frac{3}{8} \times \frac{3}{4} = \frac{{2 \times 3 \times 3}}{{5 \times 8 \times 4}} = \frac{{18}}{{160}} = \frac{9}{{80}}$
b) $\frac{1}{3} \times \frac{1}{6} \times \frac{1}{9} = \frac{{1 \times 1 \times 1}}{{3 \times 6 \times 9}} = \frac{1}{{162}}$
c) $\frac{3}{4}:\frac{1}{5}:\frac{7}{8} = \frac{3}{4} \times \frac{5}{1} \times \frac{8}{7} = \frac{{3 \times 5 \times 8}}{{4 \times 1 \times 7}} = \frac{{120}}{{28}} = \frac{{30}}{7}$
d) $\frac{3}{5}:\frac{1}{5}:\frac{3}{8} = \frac{3}{5} \times \frac{5}{1} \times \frac{8}{3} = \frac{{3 \times 5 \times 8}}{{5 \times 1 \times 3}} = 8$
\(\dfrac{1}{3}\)x 2\(\dfrac{1}{5}\) + \(\dfrac{1}{3}\) x ( -0,8)
= \(\dfrac{1}{3}\) x ( 2\(\dfrac{1}{5}\) - 0,8)
= \(\dfrac{1}{3}\) x ( \(\dfrac{11}{5}\) - \(\dfrac{4}{5}\))
= \(\dfrac{1}{3}\) x \(\dfrac{7}{5}\)
= \(\dfrac{7}{15}\)